2013
DOI: 10.1186/1471-213x-13-13
|View full text |Cite
|
Sign up to set email alerts
|

miRNA regulated pathways in late stage murine lung development

Abstract: BackgroundMicroRNAs play important roles in regulating biological processes, including organ morphogenesis and maturation. However, little is known about specific pathways regulated by miRNA during lung development. Between the canalicular and saccular stages of the developing lung several important cellular events occur, including the onset of surfactant synthesis, microvascular remodeling and structural preparation for subsequent alveolarization. The miRNAs that are actively regulated, and the identity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 55 publications
1
37
0
Order By: Relevance
“…Mele et al identified 92 protein-coding genes differentially expressed in males and females across multiple human tissues [22]. In agreement with human studies, Yang et al identified 2871 genes from the mouse genome with differential expression by sex in multiple somatic tissues [23,24], while another study identified 25 of 376 miRNAs in fetal mouse lung that were also differentially expressed by sex [25]. Sex-specific differences were also shown for DNA methylation and histone acetylation.…”
supporting
confidence: 63%
“…Mele et al identified 92 protein-coding genes differentially expressed in males and females across multiple human tissues [22]. In agreement with human studies, Yang et al identified 2871 genes from the mouse genome with differential expression by sex in multiple somatic tissues [23,24], while another study identified 25 of 376 miRNAs in fetal mouse lung that were also differentially expressed by sex [25]. Sex-specific differences were also shown for DNA methylation and histone acetylation.…”
supporting
confidence: 63%
“…However, due to the effect of androgens on branching morphogenesis (11), it is possible that, earlier in gestation, the development of the male lung is more advanced than in the female. MicroRNAs that are significantly different between sexes during murine lung development have been identified (28). We previously determined that genes that are important in lung development might be associated with lung function in subjects with asthma (9).…”
Section: Discussionmentioning
confidence: 99%
“…Two miRNAs: miR-146 and miR-203 are associated with psoriasis and have specific pattern of expression in patients (Sonkoly et al, 2007;Nestle et al, 2009). Rheumatoid arthritis (RA) characterized by chronic inflammation of synovial tissue was also reported by various studies to be associated with miR-155, miR-146, miR-132, miR16, miR-346 and miR-223 expression change compared with healthy people (Alsaleh et al, 2009;Pauley et al, 2009;Fulci et al, 2010).…”
Section: Mirnas and Autoimmune Diseasesmentioning
confidence: 99%
“…The first four stages occur during gestation, and the final stage starts at 24 th week and continues through early childhood (Bhaskaran et al, 2009;Mujahid et al, 2013).…”
Section: Lung Development and Mirnasmentioning
confidence: 99%
See 1 more Smart Citation